Non-communicable Diseases in Nepal: Challenges and Opportunities - Neupane D, Kallestrup P (Journal of Nepal Health Research Council, 2013)
Non-communicable diseases constitute a major public health problem in Nepal. They are already killing more people than communicable diseases. However, addressingn on-communicable diseases is not getting much attention from the government, academicians and development partners.Simple measures at population and individual level have not been implemented in an effective way. The vision on how to address non-communicable diseases at primary health care level is unclear. However, there is aunique possibility of integrating non-communicable diseases into the existing communicable diseases interventions which need to be tested and potential positive lessons have to be scaled up as soon as possible. The best buy approach as proposed by WHO could be implemented for non-communicable diseases prevention and management through primary health care approach.